Öffentliche Landwirtschaft in Syrien: Staatsfarmen als Beispiele für die Wirksamkeit staatlicher Wirtschaftstätigkeit im Agrarsektor des Landes - Hopfinger, Hans (ERDKUNDE, 1990)
State farms are fully integrated elements of Syria's agricultural system as well as of the country's national economy. It is a centrally planned and controlled socialist economy, in which government activities play a crucial role: state farms are supposed to allow direct government intervention in the country's agricultural development. The results of this report can be summarized as follows: (i) As part of a centrally planned system, the state farms have to stick to detailed production plans. Free economic decision-making is almost impossible for the farms: specific production targets have to be achieved even if it is against the management's conviction, (ii) Most of the farms partly lack the required equipment for efficient production or waste a lot of financial ressources for repairing outdated machines and irrigation devices, (iii) By comparison with private enterprises, the labour force in state farms is large whereas its efficiency and qualification are considerably lower. It reflects the low level of fixed payment in the public sector of Syria's economy, (iv) The economic performance of most of the state farms - even the model enterprise Al Asad in Maskana - is characterized by losses. Since 1980 only the farm in Maliklya in Northeast Syria has been able to present positive results for every agricultural season.